Oral magnesium supplementation for leg cramps in pregnancy-An observational controlled trial. - Carla Adriane Leal de Araújo; Suélem Barros de Lorena; Guilherme Camelo de Sousa Cavalcanti; Gabriel Landim de Souza Leão; Geraldo Padilha Tenório; João Guilherme B Alves (PLoS ONE)
Background Oral magnesium for leg cramps treatment in pregnancy is a controversial issue according to recent Cochrane systematic review. This study aims to evaluate the efficacy of Mg++ supplementation in leg cramps treatment in pregnancy. Methods This observational clinical trial studied 132 pregnant women with leg cramps in the first trimester of pregnancy. At baseline, 74 (56.3%) had two leg cramps episodes per week, 28 (21.1%) three episodes, 13 (9.8%) four episodes and 9 (6.8%) five or more episodes. They were randomized 1:1 to 300 mg/day of oral Mg++ citrate (n = 66) or placebo (n = 66). The primary outcome was the frequency of leg cramps episodes per week reported by pregnant women. Secondary outcomes were the ocurrence of leg cramps and oral magnesium side effects. Results 130 pregnant women completed the study and the two groups were comparable according to some sociodemographic and clinical characteristics. After 4 weeks of intervention it was observed a 28.4% (39/132) (CI 95%: 20.9-37.0) reduction of leg cramps in all participants and no difference between the two groups was found; reduction of 27.2% (18/66) (CI 95%: 17.0-39.6) in Mg++ group and 32.8% (21/66) (CI 95%: 21.6-45.7) in the placebo group. The OR of leg cramps was 1.3 (CI 95%: 0.6-2.9), p = 0.527, taking the placebo group as reference. Among pregnant women who remained with leg cramps the mean of leg cramps episodes per week showed no significance difference between the Mg++ and placebo groups; t-student test: p = 0.408. Four pregnant women showed gastrointestinal side effects; 2 in each group had nauseas and diarrhoea. Conclusion Oral magnesium supplementation during pregnancy did not reduce the ocurrence and frequency of episodes of leg cramps.